Analisis Bibliometrik pada Jurnal Al-Maktabah, Pustakaloka, Unilib & Libraria Periode 2015-2021 - R. Suhendani; Rochani Nani Rahayu (Al-Ma'mun, 2022)
A bibliometric analysiss was conducted to determine 1) the number of articles published annualy from 2015-2021;2) the number of authors who contributed to the four journals for tha 2015-2021 peroid;30 the productivity of writers in the four journals for the 2015 – 2021 period, for the journals in the field of library, documentation and information, respectively are ALMAKTABAH, PUSTAKALOKA, UNILIB & LIBRARIA. Data sources are accessed from each of the journal sites, https://journal.iainkudus.ac.id/index.php/Libraria, https://journal.uii.ac.id/unilib, https://jurnal.iainponorogo.ac.id/index.php/pustakaloka/index, dan https://journal.uinjkt.ac.id/index.php/al-maktabah/index. The result of this research is the total number of articles published in ALMAKTABAH, PUSTAKALOKA, UNILIB & LIBRARIA, 377 titles, consisting of 69, 115, 72 and 121 titles, respectively The total authors are 529 people consisting of . Almaktabah 104 authors, Pustakaloka 161 authors, Unilib 87 authors and Libraria 177 authors. The most prolific authors of the AlMaktabah journal are U Undayani (7 articles) from UIN Syarif Hidayatullah Jakarta, L Lolytasari (5 articles) from UIN Syarif Hidayatullah Jakarta, R Rodin (4 articles) IAIN Curup-Rejang Lebang Bengkulu, then A Alfida and L Istiqoriyah (3 articles) each from UIN Syarif Hidayatullah Jakarta, and 2 other authors from UIN Imam Bonjol and UIN Sunan Kalijaga. The pattern of authorship shows that from a total of 377 articles, single authors (259 articles 0.69%) and collaborating authors (118 articles 0.31%) with an average collaboration degree of 0.31. The conclusion of the study is that during 2015-2021, 377 articles have been written from four journals (ALMAKTABAH, PUSTAKALOKA, UNILIB & LIBRARIA), written by 529 authors mostly written individually, and the most productive authors are U Undayani (7 articles), writes at AlMaktabah UIN Syarif Hidyatullah